2009
DOI: 10.1007/s11556-009-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and health in frail elderly people: a review of randomized controlled trials

Abstract: Frailty is a physiological syndrome that increases the risk of poor health. Although some research has been conducted to study the benefits of physical exercise in frail elderly populations, different operational definitions of frailty have been used, and this makes the studies difficult to compare. The present review was aimed at examining the influence of exercise on health in frail older adults. Studies using randomized controlled trials that administered an exercise program to a frail elderly population an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
(171 reference statements)
0
7
0
Order By: Relevance
“…The lack of strong statistical evidence relating physical HR QoL to group activity is likely to be due to type II error from a small sample and biases of self-report surveys. However, the FG discussions suggested that participants perceived that the PA they did in their LAC program offered them significant physical health and physical capacity benefits; known to be associated with regular PA [6–8]. This contrast in results suggest that larger studies are warranted in future to confirm any association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of strong statistical evidence relating physical HR QoL to group activity is likely to be due to type II error from a small sample and biases of self-report surveys. However, the FG discussions suggested that participants perceived that the PA they did in their LAC program offered them significant physical health and physical capacity benefits; known to be associated with regular PA [6–8]. This contrast in results suggest that larger studies are warranted in future to confirm any association.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is an essential component of such strategies because of its vastly known mental and physical health benefits such as chronic disease prevention [6–8], maintenance of functional capacity and cognitive health [913]. Despite the wide-ranging benefits of participating in regular PA, global inactivity levels are high and increase with age.…”
Section: Introductionmentioning
confidence: 99%
“…Because a low level of physical activity is strongly related to frailty, 38,39 exercise programs could be a feasible way to improve health in this population. However, the feasibility and effectiveness of exercise in frail older populations is still not well-known, 40 and further research is needed on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Performing sufficient physical activity (PA) is a primary modifiable determinant of health especially pertinent to Active Ageing because it is known to have vast mental and physical health benefits for people of all ages [ 6 , 7 ]. In adults, PA reduces the risk of all-cause mortality, prevents various chronic diseases, and in older adults especially, it reduces the risk of falls and helps maintain physical and cognitive function [ 8 – 17 ].…”
Section: Introductionmentioning
confidence: 99%